Pre-closure laryngeal properties as cues to the fortis–lenis plosive contrast in British varieties of English - Hejná, Míša; Kimper, Wendell (Yearbook of the Poznan Linguistic Meeting, 2018)
The present study contributes to our understanding of the phonetic implementation of the fortis–lenis plosive contrast in British varieties of English via analyses of pre-aspiration and glottalisation. More specifically, we show that pre-aspiration and (pre-) glottalisation can and do function as correlates of the contrast in British English plosives in non-foot-initial position (latter vs ladder; mat vs mad). This is in addition to rather than at the expense of the other traditionally discussed potential correlates, with the exception of word-final release duration, where the pre-closure laryngeal phenomena are more robust. We also provide evidence that listeners of a range of accents of British English use pre-aspiration as a cue to the contrast, exhibiting clear categorical perception effects (based on data from 19 listeners). We conclude that the gesture of spread glottis is not necessarily tied to the release phase of the plosive in the relevant varieties of British English but instead can be found prior to the release phase, or indeed both prior to as well as during the release phase itself. Our study thus contributes to the pool of languages known to use pre-closure laryngeal features functioning as correlates of and cues to phonological contrasts (see e.g. Clayton 2009; Kingston 1990; Silverman 1995).